The Marriages of the Spaniards on the Coast and Interior of Tarapaca, 1859-1940 - Calle Recabarren, Marcos Agustín (Revista de humanidades (Santiago. En línea), 2016)
This article examines the matrimonial customs of the Spanish community during 81 years in the province of Tarapaca. The analysis is carried out based on the registers and matrimonial documents of the Parish of the Immaculate Conception and the Civil Registry, which shows a close relationship between the immigration flows of male Spaniards and the high rates of endogamy which were reflected in their great tendency to marry Chileans and Peruvians. Aditionally, in the economic area the Spanish marriage partners were related with terciary activities principally commerce, through the parental and friendship migratory chains, through which they developed mecanisms and strategies of solidarity in the internal market.